Gestão de resíduos sólidos: um estudo de caso no município de Caldas Novas (GO) - Soares, Marcel (Universidade do Vale do Rio dos Sinos, 2010)
This paper aims to address the environmental problems associated with solid wastes in a hotel chain in the touristic town Caldas Novas, Goias. To conduct the study it was collected informations on the different actors involved in the issue which included public agencies and private entities, as well as on studies and experiences reported in the literature. The investigation involved the evaluation of laws and processes which involved seeking strategies for minimizing the environmental and socio-economic impacts entailed by such waste. The study concluded by the need to link the issue of solid wastes with the strategy of sustainable local tourism business. This implies the need to significantly modify the status quo. The work makes clear the need to build stock of planning and executing the current situation in order to adapt the best practices suggested in the literature and legislation to address the issue of solid waste in the hotel network in the city of Caldas Novas and surrounding areas.
Keywords: Resíduos sólidos; Gestão dos resíduos sólidos; Desenvolvimento sustentável; Caldas Novas; Solid waste; Solid wastes management; Sustainable development; ACCNPQ::Ciências Sociais Aplicadas::Administração